Simulation research on collisions between highway corrugated beam guardrails and vehicles based on LS-DYNA - Yongming He; Yanan Wan; Kun Wei; Jia Feng; Cong Quan (Digital Transportation and Safety)
To explore the safety of highway traffic operations, the vehicle state and guardrail deformation during highway guardrail collisions are simulated and analyzed. The vehicle-guardrail collision is simulated by finite element software such as LS-DYNA and HyperMesh. The vehicle speed settings are 60, 80, 100 and 120 km/h, and the collision angles are 5°, 10°, 15° and 20°. The guardrail deformation, vehicle acceleration and energy changes under different collision speeds and angles are studied. The research results show that at the same collision speed, an increase in the collision angle causes more serious damage to the vehicle, a greater transverse displacement of the guardrail, and a greater range of car acceleration fluctuations. When the collision angle is the same, an increase in the collision speed causes greater lateral displacement of the guardrail, a greater vehicle acceleration fluctuation range, and more serious vehicle damage. The results of the study can provide a reference for demonstrating highway guardrail safety.